Empowering urban development: geospatial modeling and zonation mapping in New Kabul City, Afghanistan - Amini, Mohammad; Deng, Longsheng; Hassan, Waqas; Zidane, Fatima Zahra; Zaryab, Abdulhalim; Shahzad, Arfan (Frontiers in Earth Science, 2024)
The main difficulties in urban development, choosing a location, and creating preventative safety precautions are accurately characterizing and valuing subsurface soil information from a geotechnical and geological standpoint. This paper discusses how to define and build geotechnical subsoil soil zonation maps (SZMs) for the new Kabul city, Afghanistan, using traditional ArcGIS software assessing Kriging interpolation approaches. With the city’s expansion plans, including New Kabul City’s development, our research supports informed urban development strategies. Subsoil data from 2,13 locations across the city were collected from geotechnical studies, focusing on soil classification, Standard Penetration Test (SPT-N values), undrained shear strength, and consolidation characteristics up to 15 m depth. SPT-N and soil type were used to create SZMs, and other parameters were used to evaluate bearing capacity and settlement. The results revealed that SPT-N values divided the research region into three main sections: A (8–>50), B (13–>50), and C (14–>50). The subsurface strata consist of low-plasticity clay (CL) and clayey sand (SC) underlain by highly plastic clay (CH) and silt (MH). Linear regression predicted SPT-N values with depth, showing a strong R2 of 0.95. This speeds up sub-soil stiffness and strength assessments during building project planning and feasibility studies. The shallow Kabul foundation has an allowable bearing capacity of over 100 kPa, making it suitable for lightly loaded buildings. Predicting SPT-N levels has an 85% correlation coefficient, while soil type has 94%. Accurate geotechnical data on the soil’s underlying layers will help characterize the site and identify future project risks.